How regulation based on a common stomach leads to economic optimization of honeybee foraging. (21st January 2016) - Schmickl, Thomas; Karsai, Istvan
Abstract: Simple regulatory mechanisms based on the idea of the saturable 'common stomach' can control the regulation of protein foraging and protein allocation in honeybee colonies and colony-level responses to environmental changes. To study the economic benefits of pollen and nectar foraging strategies of honeybees to both plants and honeybees under different environmental conditions, a model was developed and analyzed. Reallocation of the foraging workforce according to the quality and availability of resources (an 'adaptive' strategy used by honeybees) is not only a successful strategy for the bees but also for plants, because intensified pollen foraging after rain periods (when nectar quality is low) compensates a major fraction of the pollination flights lost during the rain. The 'adaptive' strategy performed better than the'fixed' (steady, minimalistic, and non-adaptive foraging without feedback) or the 'proactive' (stockpiling in anticipation of rain) strategies in brood survival and or in nectar/sugar economics. The time pattern of rain periods has profound effect on the supply-and-demand of proteins. A tropical rain pattern leads to a shortage of the influx of pollen and nectar, but it has a less profound impact on brood mortality than a typical continental rainfall pattern. Allocating more bees for pollen foraging has a detrimental effect on the nectar stores, therefore while saving larvae from starvation the 'proactive' strategy could fail to collect enough nectar for surviving winter. Highlights: Task regulation of collective behavior is modeled by individual ODE based approach. The colony uses 'common stomachs' that buffer and regulate foraging. The colony dynamically adapts to perturbations and changes in nutrition quality. The model predicts an adaptive strategy for both bees and plants. The mechanisms explain the self-regulating behavior of the collective.